Faktor-Faktor yang Mempengaruhi Penyesuaian Perkawinan - Amelia Suci Latifah; Zulfa Indira Wahyuni (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
The sampling technique used in this study is non-probability sampling technique that is purposive sampling. In this study used Dyadic Adjustment Scale (DAS) developed by Spanier (1976), Big Five Inventory (BFI) developed by John, O. P & Srivastava, S. (1999) and Emotional Intelligence Scale developed by Salovey & Mayer (1990). The validity of the measuring instrument was tested using the Confirmatory Factor Analysis (CFA) technique with Lisrel 8.70 software and to test the research hypothesis using multiple regression analysis using SPSS 21 software. The results of the study using multiple regression analysis showed that all independent variables used had a significant effect on marital adjustment with a variant proportion of 16.4%, while the remaining 83.6% is influenced by other variables other than research. Meanwhile, the results of the analysis of each variable separately show that the personality type variables conscientiousness and openness to experience have a significantly to marital adjustment. While personality types extraversion, agreeableness, neuroticsm, emotional intelligence, gender, duration of marriage and income not significant effect on marital adjustment.